2019
DOI: 10.3389/fpsyt.2019.00491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seclusion and Restraint in Adult Psychiatry: A Systematic Review

Abstract: Background: Determining the clinical effects of coercion is a difficult challenge, raising ethical, legal, and methodological questions. Despite limited scientific evidence on effectiveness, coercive measures are frequently used, especially in psychiatry. This systematic review aims to search for effects of seclusion and restraint on psychiatric inpatients with wider inclusion of outcomes and study designs than former reviews. Methods: A systematic search was conducted follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
4
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 85 publications
(237 reference statements)
3
172
4
9
Order By: Relevance
“…Reports of this typically negative perception of involuntary treatment are well-known from general psychiatric patients also (38,39,42). The impact of different involuntary measures on these patients seems to vary by measures, with seclusion and restraint having an especially negative impact (6,39,42). The subjective implications of nasogastric feeding specifically have in a small qualitative study been reported to increase rebellious behavior as well as involuntary measures such as restraint and forced medication (23).…”
Section: Patients' Perception Of Involuntary Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of this typically negative perception of involuntary treatment are well-known from general psychiatric patients also (38,39,42). The impact of different involuntary measures on these patients seems to vary by measures, with seclusion and restraint having an especially negative impact (6,39,42). The subjective implications of nasogastric feeding specifically have in a small qualitative study been reported to increase rebellious behavior as well as involuntary measures such as restraint and forced medication (23).…”
Section: Patients' Perception Of Involuntary Treatmentmentioning
confidence: 99%
“…As described below, involuntary treatment is usually evaluated negatively by patients, professionals, and relatives (6)(7)(8)(9)(10). Inpatient care must thus always aim to find alternative strategies and interventions to involuntary treatment, reducing it whenever possible without neglecting its lifesaving purpose and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, ethical and legal questions raises from overriding a person's will. These coercive measures limit several fundamental human rights, such as liberty of choice or movement, autonomy, and physical integrity 9,10 . An estimated 10% of psychiatric patients in Jordan were restrained or secluded at least once during their admission to psychiatric settings, and countless others are injured or traumatized 11 .…”
Section: Introductionmentioning
confidence: 99%
“…2 When participants offered analogies to the ED experiences in which they were restrained, they compared them to incarceration or childhood abuse, not a therapeutic encounter; many described lingering problems with hypervigilance and flashbacks, 2 symptoms of incipient posttraumatic stress disorder that can be induced by physical restraints. 4 Some patients said they had learned that being restrained is an inevitable outcome of receiving treatment in the ED. The study did not report how many participants had been restrained previously, but the perception that a negative outcome is inevitable is reminiscent of the learned helplessness Such conversations might lead to restorative justice approaches, during which patients and staff could come together after an event in a therapeutic encounter that would acknowledge the potential necessity of coercive acts within medicine while working together to avoid future negative outcomes.…”
mentioning
confidence: 99%